(untitled) - Syngress Media, Inc. (Berkeley, Calif., 1998)
Though intimidating at first glance, all misgivings fall away once you begin traversing the pages of the Network+ Certification Study Guide. This book is laid out exceptionally well, with each chapter divided into certification objectives such as network operating systems, network protocols, and password practices and procedures.
Keywords: Phần mềm Microsoft,Computer networks; Kiểm tra,Hướng dẫn học tập,Examinations,Study guides